1991
DOI: 10.1007/bf00180646
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical studies of morpholine catabolism by an environmental mycobacterium

Abstract: When Mycobacterium strain MorG was grown with morpholine as sole source of carbon and nitrogen, enzymes for ethanolamine catabolism (via the ethanolamine-O-phosphate pathway) and glycollate catabolism (via the glycerate pathway) were strongly induced. Almost all morpholine-negative (Mor-) mutants of MorG failed to utilize glycollate as a carbon source and were shown to be defective in one or more enzymes for its metabolism via the glycerate pathway. Growth of MorG with morpholine also induced the Jacoby and Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…strain MORG. These results clearly show that the ethanolamine branch proposed previously (20,24) as a downstream pathway for morpholine degradation is not present. Indeed, cleavage of 2-(2-aminoethoxy)acetate in ethanolamine would be accompanied by production of oxalate without diglycolate.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…strain MORG. These results clearly show that the ethanolamine branch proposed previously (20,24) as a downstream pathway for morpholine degradation is not present. Indeed, cleavage of 2-(2-aminoethoxy)acetate in ethanolamine would be accompanied by production of oxalate without diglycolate.…”
Section: Resultssupporting
confidence: 57%
“…Indeed, cleavage of 2-(2-aminoethoxy)acetate in ethanolamine would be accompanied by production of oxalate without diglycolate. Actually, although the enzymes of this pathway branch are naturally present in mycobacteria (24), no intermediate of ethanolamine degradation was found when the cells were incubated with morpholine (7,21). Also, Swain et al (24) showed that only the enzymes of the glycolate branch were knocked out in Mycobacterium sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in κ-carrageenan, taking advantage of the oxygen gradient inside the entrapment beads (Dos Santos et al 1996a, b). The immobilisation of M. aurum in κ-carrageenan and its use in an air-bubble fermenter resulted in an improvement of its morpholine-degrading capacity (Swain et al 1991;Poupin et al 1996). The carrageenan gel and immobilised microbial cells method was used for 4-chlorophenol degradation (Wang et al 1997).…”
Section: Cleaning Of Industrial Effluentsmentioning
confidence: 99%
“…EDTA, morpholin, tetrahydrofuran, dioxane or glycol ethers), or referred to "acknowledged problems" during the biotreatment. Although cultures of naturally occurring organisms capable of degrading these substrates are known [5,6], establishing these bacteria within a degradative community seems to be difficult. Among other factors, incompatible surface properties of the different bacterial strains could be responsible for these problems.…”
Section: Introductionmentioning
confidence: 99%